2004
DOI: 10.1116/1.1752905
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium nitride/silver nanocomposite structures for biomedical applications

Abstract: Silver zirconium nitride films deposited by unbalanced magnetron sputtering were studied by means of x-ray diffraction, transmission electron microscopy, x-ray photoelectron spectroscopy, spectroscopic ellipsometry, and nanoindentation. Coatings were deposited on silicon substrates at room temperatures with bias voltages in the −45 to −160 V range. The concentration of zirconium and silver was regulated by controlling the power to the sputtering guns. The nitrogen concentration was selected so that the nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…Fig. 3 depicts the complex refractive index of the samples showing considerable differences predominantly in the imaginary part k. The results are similar to values reported by Aouadi and Debessai [7], while the advantage of a broad-band measurement is clearly visible. Figure 3.…”
Section: Spectroscopic Ellipsometrysupporting
confidence: 78%
See 1 more Smart Citation
“…Fig. 3 depicts the complex refractive index of the samples showing considerable differences predominantly in the imaginary part k. The results are similar to values reported by Aouadi and Debessai [7], while the advantage of a broad-band measurement is clearly visible. Figure 3.…”
Section: Spectroscopic Ellipsometrysupporting
confidence: 78%
“…Figure 3. Optical properties of TaN films and Ta 2 N/Ta 4 N samples compared with literature data [7].…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 99%
“…For example, for conductive materials information on the electric film properties such as resistivity and electron mean free path can be extracted during the deposition process. 21 This kind of information has recently also been extracted by SE for sputtered TaN x films, as reported by Aouadi and Debessai 22 and Mistrik et al 23 The plasma-assisted ALD process also yields the possibility to use plasma-related diagnostics during the plasma exposure step. In our previous work on plasmaassisted ALD of Al 2 O 3 from a metal-organic precursor and O 2 plasma, we showed that optical emission spectroscopy can yield information on the ALD reaction mechanisms and the timing of the plasma step.…”
Section: Introductionmentioning
confidence: 90%
“…For TaN x , the two Lorentz oscillators account for interband absorptions around 2.2 and 6.4 eV. 22,23 The imaginary ͑ 2 ͒ part of the dielectric function for a typical TaN x film with a low resistivity is shown in Fig. 2͑a͒ and the contributions of the Drude and Lorentz oscillators are indicated.…”
Section: Conductive Tan X Filmsmentioning
confidence: 99%
See 1 more Smart Citation